2021
DOI: 10.1002/fsn3.2318
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted extraction of boulardii yeast cell wall polysaccharides: Characterization and its biological functions on early‐weaned lambs

Abstract: Firstly, this study was designed to determine the optimal ultrasound‐assisted extraction parameters of Saccharomyces boulardii yeast wall polysaccharides (BYWP). Besides, the molecular weight and the ratio of mannose to glucose in compositions of BYWP were determined. Also, the effects of BYWP on the gain feed ratio, diarrhea frequency, intestinal morphology, intestinal immunity, and intestinal microbial flora of early‐weaned lambs were investigated. Single‐factor tests and Response surface optimization analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In general, weaning stress adversely affects the growth performance of kids by reducing feed intake, feed efficiency, immune suppression and increasing intestinal damage [ 17 , 18 ]. In our study, dietary fucoidan administration had no significant effects on growth performance among treatments during days 1 to 15.…”
Section: Discussionmentioning
confidence: 99%
“…In general, weaning stress adversely affects the growth performance of kids by reducing feed intake, feed efficiency, immune suppression and increasing intestinal damage [ 17 , 18 ]. In our study, dietary fucoidan administration had no significant effects on growth performance among treatments during days 1 to 15.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we used a suckling lamb model to study the promoting effects of FWBPs on growth performance and rumen development by manipulating rumen bacterial community. A previous study showed that that the addition of boulardii yeast cell wall polysaccharides in MR increased the ADG and feed conversion rate of early-weaned lambs ( 23 ). Consistent with the previous results, we demonstrated that FWBPs administration increased the ADG, final BW, and carcass BW and decreased the F:G ratio in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Oligosaccharides promote the formation of beneficial bacteria in the intestine, inhibit the proliferation of pathogenic bacteria and regulate the intestinal flora as a way to maintain intestinal health. Study found that adding 0.3% and 0.5% Saccharomyces boulardii yeast wall polysaccharides to the diet could significantly suppressed the growth of Salmonella and Clostridium perfringens in early weaned lambs [ 73 ]. The above findings suggest that probiotics inhibit the growth of harmful bacteria in the intestine tract while increasing the number of dominant bacteria, maintaining the balance of the intestinal flora and thus improving animal health.…”
Section: Mechanisms Of Action Of Probioticsmentioning
confidence: 99%